The association between vitamin D and uterine fibroids: A mendelian randomization study - Guo, Weijie; Dai, Mengyuan; Zhong, Zhuoling; Zhu, San; Gong, Guidong; Chen, Mei; Guo, Junling; Zhang, Yaoyao (Frontiers in Genetics, 2022)
Uterine fibroids (UFs), the most common benign gynecological tumor, can bring severe negative impacts on a woman's life quality. Vitamin D, is thought to play an important role in regulating cell proliferation and differentiation. In recent years, several studies suggested that higher level of vitamin D has a negative effect on the occurrence of UFs , but the results of studies on the relationship between them are conflicting and further evidence needs to be studied. Here in, we used a two-sample Mendelian Randomization (2TSMR2SMR) study to explore the causal relationship between genetically predicted vitamin D levels and the risk of UFs. The exposure data comes from a genome-wide association study (GWAS) summary dataset consisting of 441,291 individuals, which includes datasets from United Kingdom Biobank, FinnGen Biobank and the corresponding consortia. Single-nucleotide polymorphisms (SNPs) associated with vitamin D at a significant level of P<5×10-8 and low linkage disequilibrium (LD) level (r2<0.01) were selected. The outcome data comes from a GWAS dataset of IEU analysis of UK Biobank phenotypes consisting of 7,122 UFs cases and 455,811 controls. Our inverse-variance weight (IVW) analysis results support the causal association of genetically predicted vitamin D with the risk of UFs (OR=0.995,95%CI=0.990-0.999, P=0.024). In addition, heterogeneity and pleiotropy were not observed in statistical models. In summary, our results indicate that elevated serum vitamin D levels are in strong relationship with significant reduction of the risk of UFs, which indicates that the clinical treatment of UFs may have a new and excellent option.